(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The Ministry of Health and Family Welfare, Government of India, appoints Accredited Social Health Activists (ASHAs) as health facilitators under the National Rural Health Mission. Local women are chosen and trained at the village level to provide health awareness and services. Their familiarity with the local culture and socioeconomic status of families or individuals allows them to effectively communicate health-related information and mobilize households to engage with formal healthcare services. The ASHAs perform a wide range of tasks, such as providing basic healthcare information, family welfare, immunisation services, maternal and child health promotion, health counselling, maintaining health records, and community-based health projects. By serving as a vital conduit between the rural community and the public health system, they are significant backers of India's National Rural Health Mission. In Kerala, ASHAs now play a much larger role, which puts more strain on their time and energy. Their pay is primarily determined by their performance. This study examines the social cost–benefit relationship and job satisfaction of ASHA workers in Kerala, focusing on the timeliness of incentives, perceived workload, and their influence on community contribution. A total of 300 samples were selected from fourteen districts of Kerala. Primary data were analysed using descriptive statistics, Pearson correlations, and Ordinary Least Squares (OLS) regression. The study finds that timely incentive distribution and manageable workload are key determinants of job satisfaction, which in turn enhances community participation. The results highlight the need for timely payments and workload rationalisation to strengthen ASHAs’ motivation and optimise their contribution to public health delivery.